Modification of neurobehavioral effcts of Mercury By a genetic polymorphism of coproporphyrinogen oxidase in children - Woods, James S. (2012)
Mercury (Hg) is neurotoxic, and children may be particularly susceptible to this effect. A current major challenge is the identification of children who may be uniquely susceptible to Hg toxicity because of genetic disposition. We examined the hypothesis that CPOX4, a genetic variant of the heme pathway enzyme coproporphyrinogen oxidase (CPOX) that affects susceptibility to mercury toxicity in adults, also modifies the neurotoxic effects of Hg in children. Five hundred seven children, 8–12 years of age at baseline, participated in a clinical trial to evaluate the neurobehavioral effects of Hg from dental amalgam tooth fillings in children. Subjects were evaluated at baseline and at 7 subsequent annual intervals for neurobehavioral performance and urinary mercury levels. Following the completion of the clinical trial, genotyping assays for CPOX4 allelic status were performed on biological samples provided by 330 of the trial participants. Regression modeling strategies were employed to evaluate associations between CPOX4 status, Hg exposure, and neurobehavioral test outcomes. Among girls, few significant CPOX4-Hg interactions or independent main effects for Hg or CPOX4 were observed. In contrast, among boys, numerous significant interaction effects between CPOX4 and Hg were observed spanning all 5 domains of neurobehavioral performance. All underlying dose-response associations between Hg exposure and test performance were restricted to boys with the CPOX4 variant, and all of these associations were in the expected direction where increased exposure to Hg decreased performance. These findings are the first to demonstrate genetic susceptibility to the adverse neurobehavioral effects of Hg exposure in children. The paucity of responses among same-age girls with comparable Hg exposure provides evidence of sexual dimorphism in genetic susceptibility to the adverse neurobehavioral effects of Hg in children and adolescents.